Rocket Observation of Aurora (Reports of the Japanese Antarctic Research Expedition) - Eisuke KANEDA (National Institute of Polar Research, 1972)
After a brief comment on the recent progress in the morphological study of substorm, it is stated that rocket observations must be conducted in connection with the study of synoptic auroral features. The observation of O_2 IR Atmospheric (0,0) 1.27 μ is especially important as a target of synthetic researches on magneto-ionospheric coupling. Finally, the aurora monitoring at for rocket position by an automatic TV camera is recommended as an enhanced ground observation during the flight.